2024
DOI: 10.2147/amep.s448422
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice Toward Artificial Intelligence Among Healthcare Workers in Private Polyclinics in Jeddah, Saudi Arabia

Suhail Hasan Surbaya,
Adeel Ahmed Khan,
Saud Hasan Surbaya
et al.

Abstract: Purpose The objective of our study was to assess awareness, attitudes, and practices regarding artificial intelligence (AI) among healthcare workers in private polyclinics in Jeddah, Saudi Arabia. Methods We conducted cross-sectional study among healthcare workers in private clinics in Jeddah. Data was collected using a structured, validated questionnaire in Arabic and English on awareness, attitudes, and behaviors regarding AI. Cronbach’s alpha for the questionnaire ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…This study supports the findings of Serbaya et al (2024) that healthcare professionals generally had positive attitudes and a good awareness of AI [ 30 ]. Furthermore, another research study revealed that most healthcare professionals had a good attitude about using AI in healthcare but did not consider it dangerous to their jobs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study supports the findings of Serbaya et al (2024) that healthcare professionals generally had positive attitudes and a good awareness of AI [ 30 ]. Furthermore, another research study revealed that most healthcare professionals had a good attitude about using AI in healthcare but did not consider it dangerous to their jobs.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, this study shows a statistically significant difference between Perception of AI, ethical awareness, innovation, and gender, in which male nurses have higher mean scores in all variables than female nurses, which means male nurses are more aware of AI uses and applications used in healthcare organizations than female nurses. This finding aligns with the findings of Serbaya et al (2024), which indicate that male healthcare professionals scored higher on AI knowledge tests than female healthcare workers (Beta = 0.555, 95%, p-value = 0.010) [ 30 ].…”
Section: Discussionsupporting
confidence: 91%